Plant Defensin γ-Thionin Induces MAPKs and Activates Histone Deacetylases in Bovine Mammary Epithelial Cells Infected With Staphylococcus aureus - Báez-Magaña, Marisol; Alva-Murillo, Nayeli; Medina-Estrada, Ivan; Arceo-Martínez, María Teresa; López-Meza, Joel E.; Ochoa-Zarzosa, Alejandra (Frontiers in Veterinary Science, 2020)
Defensins are an important group of host defense peptides. They have immunomodulatory properties, which have been mainly described for mammal defensins, but similar effects for plant defensins remain unknown. Previously, we showed that the defensin g-thionin (Capsicum chinense) reduces Staphylococcus aureus internalization into bovine mammary epithelial cells (bMECs) while inducing Toll-like receptor 2 (TLR2) modulating the inflammatory response. Here, we analyze the effect of g-thionin on TLR2 pathway in bMECs infected with S. aureus and determine if it modulates epigenetic marks. Pretreated-bMECs with g-thionin (100 ng/ml) reduced the basal activation of p38 and ERK1/2 (~3 fold), but JNK was increased (~1.5-fold). Also, infected bMECs induced p38 but this effect was reversed by g-thionin; whereas ERK1/2 was reduced by infection but stimulated by g-thionin. Likewise, g-thionin reduced the activation of Akt kinase ~50%. Furthermore, g-thionin induced the activation of transcriptional factors of inflammatory response, highlighting EGR, E2F-1, AP-1 and MEF; which were turn off by bacteria. Also, g-thionin induced the activation of histone-deacetylases (HDACs, ~4 fold) at 24 h in infected bMECs, and reduced LSD1 demethylase (HDMs, ~30%) activity. Altogether, these results demonstrated by the first time that a plant defensin interferes with inflammatory signaling pathways in mammalian cells.